FACTORS OF EFFECTIVE PUBLIC-PRIVATE AND SOCIAL PARTNERSHIP IN EDUCATION (Innovative professional education, 2023)
The article raises the issue of regulatory stimulation of entrepreneurs to effectively interact with vocational education institutions on the basis of public-private and social partnership through the adoption of the laws "On fairness at work" and "On self-regulatory organizations", which will create prerequisites for the development and implementation of standards of professional activity and professional standards as tools for measuring and stimulating the effectiveness of education and work of all employees, enterprises and educational institutions.
Keywords: public-private and social partnership, professional education and the labor market